Predictive Value of Combined Preoperative Carcinoembryonic Antigen Level and Ki-67 Index in Patients With Gastric Neuroendocrine Carcinoma After Radical Surgery - Xie, Jianwei; Zhao, YaJun; Zhou, Yanbing; He, Qingliang; Hao, Hankun; Qiu, Xiantu; Zhao, Gang; Xu, Yanchang; Xue, Fangqin; Chen, Jinping; Su, Guoqiang; Li, Ping; et al. (Frontiers in Oncology, 2021)
Background: To analyze the long-term outcomes of patients with grade 3 GNEC who underwent curative surgery and investigated whether the combination of carcinoembryonic antigen (CEA) levels and Ki-67 index can predict the prognosis of patients with gastric neuroendocrine carcinoma (GNEC) and constructed a nomogram to predict patient survival. Methods: In the training cohort, data were collected from 405 patients with GNEC after radical surgery at seven Chinese centers. A nomogram was constructed to predict long-term prognosis. Data for the validation cohort were collected from 305 patients. Results: The 5-year overall survival (OS) was worse in the high CEA group than in the normal CEA group (40.5% vs 55.2%, p=0.013). The 5-year OS was significantly worse in the high Ki-67 index group than in the low Ki-67 index group (47.9% vs 57.2%, p=0.012). Accordingly, we divided the whole cohort into a KC(-) group (low Ki-67 index and normal CEA) and KC(+) group (high Ki-67 index and/or high CEA). The KC(+) group had a worse prognosis than the KC(-) group (64.6% vs 46.8%, p<0.001). KC(+) and the AJCC 8th stage were independent factors for OS. Then, we combined KC status and the AJCC 8th stage to establish a nomogram; the C-index and area under the curve (AUC) were higher for the nomogram than for the AJCC 8th stage (C-index: 0.660 vs 0.635, p=0.005; AUC: 0.700 vs 0.675, p=0.020). The calibration curve verified that the nomogram had a good predictive value, with similar findings in the validation groups. Conclusions: The nomogram based on KC status and the AJCC 8th stage predicted the prognosis of patients with GNEC well.